Application Integration 360Â° Method Feedback and Analytical Hierarchy Process as a Performance Assessment of Employees - Syatoriah, Chumayrotus; Wahyani, Widhy (Universitas KH. A. Wahab Hasbullah, 2017)
Human Resources (HR) in a companies and industry is needed to create high competitiveness based on performance results conducted on the company and the industry. In an effort to improve the quality of human resources, a company needs to conduct performance appraisals. Therefore, the Cooperative